STUDI HUBUNGAN ANTARA VOLUME, KECEPATAN DAN KEPADATAN PADA RUAS JALAN SLAMET RIYADI SAMARINDA - TANTI, YUSTIANA (KURVA S JURNAL MAHASISWA, 2017)
The movement of traffic flows on a road segment and the ability of a road segment to accommodate the flow of traffic need to be considered, and it will relate to quality and quantity of a transportation system. Volume (V), Speed (S), and Density (D) are the three main parameters that greatly affect the operational characteristics of the traffic flow. This relation between volume, speed and density can be used as a guide to determine the mathematical value of road segment for ideal conditions..............This study used comparative analysis with 3 (three) models, there are Greenshields, Greenberg and Underwood. Primary data is looking for on Slamet Riyadi Street Samarinda by survey of traffic volume and travel time on Monday, Wednesday, Saturday and Sunday from 07:00 to 09:00, at 11:00 to 13:00, and at 16:00 to 18:00 with intervals of 5 minutes every roads..............Based on the analysis and statistical test of the determinant value (R2), for the North uses Underwood relationship model with the determinant coefficient value (R2) = 0,525 which is gives the best accuracy rate of maximum speed is 21.115 km / hour, maximum density is 12,460 pcu/ km, and maximum volume is 263,101 pcu / hour. For the south uses underwood relationship model with the determinant coefficient value (R2) = 0.424 from the maximum speed is 19.707 km / hour, the maximum density is 14.293 pcu /km, and the maximum volume is 281,679 pcu / hour.